2011
DOI: 10.1093/arclin/acr043
|View full text |Cite
|
Sign up to set email alerts
|

A Context for Normalizing Impulsiveness at Work for Adults with Attention Deficit/Hyperactivity Disorder (Combined Type)

Abstract: Impaired executive function and impulsiveness or intolerance to boredom in adult attention deficit/hyperactivity disorder (ADHD) are thought to compromise performance at work. Several task parameters help people with ADHD to perform better on computerized cognitive tasks, namely reduced response-to-stimulus interval, discriminative feedback, or a format resembling a videogame. However, still very little is known about how these contexts might be helpful in a real work environment. We developed a computerized t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 54 publications
0
27
0
Order By: Relevance
“…Delisle and Braun, 2011). Much like our subjects describe, situations that are particularly motivating—fast-paced, challenging, novel—have been shown in laboratory settings to improve performance and reduce symptoms in these individuals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Delisle and Braun, 2011). Much like our subjects describe, situations that are particularly motivating—fast-paced, challenging, novel—have been shown in laboratory settings to improve performance and reduce symptoms in these individuals.…”
Section: Discussionmentioning
confidence: 99%
“…This model hypothesizes that, rather than a static “attention deficit” in all contexts, affected individuals have a higher threshold for “motivational salience,” becoming bored easily when performing uninteresting or menial tasks (Delisle and Braun, 2011, Sonuga-Barke, 2005). Thus, “ADHD is not characterized by an inability to sustain attention, but rather by the inability to appropriately regulate the application of attention to tasks that are not intrinsically rewarding and/or that require effort” (Kaufmann and Castellanos, 2000, p. 624).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, most adults with ADHD will manage best in an environment that provides some fl exibility within the context of a clear structure and set of rules to follow (Barkley 2010 ). Clinical observations (Barkley 2010 ;Murphy 2005 ;Nadeau 1997 ) and results of a simulated workplace experience (Delisle and Braun 2011 ) have suggested that adults with ADHD perform best in occupations that have constant action demands rather than understimulating or repetitive work. The externally generated cues of a more lively setting can provide much-needed stimulation and also help to structure one's activities, thus reducing the need to organize and initiate activities independently.…”
Section: Job Selectionmentioning
confidence: 99%
“…At the same time, a balance is required to avoid overstimulation as clinical observations suggest that stress has the potential to worsen ADHD symptoms (Nadeau 1997 ). Also pertinent is having some clear means to evaluate work performance as adults with ADHD were more likely to seek out discriminative feedback in a workplace simulation experiment (Delisle and Braun 2011 ). Incentives and rewards may be particularly important to adults with ADHD; if not directly built into the job, it may be helpful to set up a feedback system, perhaps with a close mentor or supervisor, to provide such tangible rewards to help structure and prioritize their work.…”
Section: Job Selectionmentioning
confidence: 99%